2021
DOI: 10.3390/biology10060524
|View full text |Cite
|
Sign up to set email alerts
|

Specific Bioelectrical Impedance Vector Analysis Identifies Body Fat Reduction after a Lifestyle Intervention in Former Elite Athletes

Abstract: Background: specific bioelectrical impedance vector analysis (BIVA) has been proposed as an alternative bioimpedance method for evaluating body composition. This investigation aimed to verify the ability of specific BIVA in identifying changes in fat mass after a 16-week lifestyle program in former athletes. Methods: The 94 participants included in the Champ4life project (clinicaltrials.gov: NCT03031951) were randomized into intervention (n = 49) and control (n = 45) groups, from which 82 athletes completed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The combined evaluation of R and Xc as a vector within a graph results in a qualitative evaluation of body composition, defined as bioelectrical impedance vector analysis (BIVA) [ 19 ]. In BIVA, the position of the vector is interpreted in relation to its lateral and vertical displacements, which are reflected by phase angle (PhA) and vector length, respectively [ 15 , 20 , 21 , 22 ]. Several studies on soccer players have shown that PhA is related to sprint performance [ 11 , 12 ] and that BIVA patterns allow for the evaluation of nutritional status and physical condition during the competitive season [ 13 , 21 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The combined evaluation of R and Xc as a vector within a graph results in a qualitative evaluation of body composition, defined as bioelectrical impedance vector analysis (BIVA) [ 19 ]. In BIVA, the position of the vector is interpreted in relation to its lateral and vertical displacements, which are reflected by phase angle (PhA) and vector length, respectively [ 15 , 20 , 21 , 22 ]. Several studies on soccer players have shown that PhA is related to sprint performance [ 11 , 12 ] and that BIVA patterns allow for the evaluation of nutritional status and physical condition during the competitive season [ 13 , 21 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study provides BIA data of an elite sample of young male and female handball players, which may help determine target regions of bioelectrical impedance vectors for young handball players. As a result, trainers can plan specific training programs to induce appropriate vector migration [ 21 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…BIVA interpolates R and Xc, standardized for the subject height, on the RXc graph as a single vector, to assess soft tissues and body fluids. This qualitative analysis allows comparison of the position of the vector to the tolerance ellipses (representing the population reference values) and to study its displacements by collecting multiple measurements (e.g., during a season [ 24 ], after exercising [ 25 ], or over an intervention program [ 26 ]). Vector elongation or shortening over time represent decreases or increases in hydration, while lateral displacement to the left or the right reflect gains or losses in the soft tissues, respectively [ 23 ].…”
Section: Introductionmentioning
confidence: 99%